Answer:
<em> 3(x+y)+15xy</em>
<em></em>
Step-by-step explanation:
Write an algebraic expression for the verbal expression: three times the sum of X and Y increase by five times the product of x and 3y.
Sum of x and y = x+y
three times the sum of X and Y = 3(x+y)
product of x and 3y = x(3y) = 3xy
five times the product of x and 3y = 5(3xy) = 15xy
<em>Three times the sum of X and Y increase by five times the product of x and 3y will be expressed as;</em>
3(x+y) + 15xy
<em>Hence the required algebraic expression is 3(x+y)+15xy</em>
<em></em>
<em></em>